2015
DOI: 10.1002/hbm.22828
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diffusion tractography and tract-tracing measures of connectivity strength in rhesus macaque connectome

Abstract: With the mapping of macroscale connectomes by means of in vivo diffusion-weighted MR Imaging (DWI) rapidly gaining in popularity, one of the necessary steps is the examination of metrics of connectivity strength derived from these reconstructions. In the field of human macroconnectomics the number of reconstructed fiber streamlines (NOS) is more and more used as a metric of cortico-cortical interareal connectivity strength, but the link between DWI NOS and in vivo animal tract-tracing measurements of anatomica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 58 publications
6
103
0
Order By: Relevance
“…However, it is questionable how informative such properties are when treating connectomes as networks, which would require some proxy of connectivity. In a recent study no correlation was found between such microstructural measures and axonal strengths measured by tracers . On the other hand, functions of streamline counts can be thought to be more relevant in such a network context .…”
Section: Building a Connectomementioning
confidence: 90%
“…However, it is questionable how informative such properties are when treating connectomes as networks, which would require some proxy of connectivity. In a recent study no correlation was found between such microstructural measures and axonal strengths measured by tracers . On the other hand, functions of streamline counts can be thought to be more relevant in such a network context .…”
Section: Building a Connectomementioning
confidence: 90%
“…First, we constructed a symmetric N × N streamline count matrix for each subject, where edge weights were equal to the number of probabilistic streamlines connecting each pair of GM-WM boundary nodes [39,74]. Second, we constructed networks where edge weights were equal to the total number of streamlines connecting a node pair divided by their total volume [48,75,76]. Third and finally, we also constructed networks where edge weights were equal to the connectivity probability between each pair of brain regions, which represents the proportion of total samples (probabilistic streamlines) initiated from the seed region that reached the target region [7779].…”
Section: Methods Detailsmentioning
confidence: 99%
“…In the monkey, whole-brain tract-tracer connection networks and tractography networks demonstrate a significant, but only moderately high correspondence. Currently, the highest reported correlation stands at r = 0.59 (Donahue et al, 2016), though it is often much lower (van den Heuvel et al, 2015a). Future work could probably improve these relationships substantially by imposing rigorous anatomical constraints in the tractography process (Smith et al, 2015), but such efforts have not seen extensive validation yet.…”
Section: The Role Of Animal Modelsmentioning
confidence: 99%